Enhancing academic self-efficacy through cognitive behavioral counseling with integrated islamic values: a study on university students - Putri, Sefni Rama; Degeng, I Nyoman Sudana; Muslihati, Muslihati; Ramli, M.; Siregar, Ilham Khairi (Universitas Ahmad Dahlan, 2025)
This study investigates the effectiveness of Cognitive Behavioral Counseling (CBC) integrated with Al-Islam and Kemuhammadiyahan (AIK) values to enhance academic self-efficacy among university students. The study utilized a single-subject research (SSR) design with an A-B-A format involving five final-year students with low academic self-efficacy. Data were collected using the College Academic Self-Efficacy Scale (CASES). Data analysis combined visual graphical inspection and the Wilcoxon signed-rank test to assess the effectiveness of the intervention. Results showed a significant increase in academic self-efficacy post-intervention, with a Wilcoxon signed-rank test revealing a Z-score of -2.060 (p < 0.05). The integration of AIK values, particularly tauhid, provided a spiritual and moral foundation, demonstrating the intervention's effectiveness. These findings suggest that CBC techniques, when combined with religious values, can positively impact students' self-efficacy and academic performance. The study contributes a culturally relevant counseling model that integrates Islamic values, offering insights for academic counseling in Islamic institutions. Future research is encouraged to explore larger samples and diverse settings.